Social and behaviour change communications strategy for improving livestock derived food consumption: IPSR Innovation Profile - Ouma, Emily A.; Omosa, Esther B.; Flax, Valerie L.; Schreiner, Mary-Ann; Colverson, Kathleen E.; Girard, Amy W.; Dominguez-Salas, Paula; Baltenweck, Isabelle (2022)
The innovation comprises approaches and gender sensitive delivery models for influencing behaviour on diets that include livestock derived foods and food safety practices through social behaviour change communication. The materials consist of counselling cards, posters, brochures with key messages that focus on: (a) The importance and benefits of animal-source foods consumption, (b) The appropriate quantities of animal-source foods to be consumed by pregnant and lactating women and young children, (c) The appropriate time to introduce animal-source foods to young children, (d) How to recognize animal-source food intolerance symptoms and treatment, (e) The importance of hygiene, food safety and storage of animal source foods. The materials and messaging were developed with a gender sensitive lens, to promote the inclusion of mothers, fathers and caregivers. The messages were delivered through community health workers, model fathers, and reminders sent through short messaging services and megaphone blasts.